Pengembangan Sistem Manajemen Pendaftaran Lomba Tingkat Pendidikan Menengah dan Tinggi - Dzaky Fadhilla Guci; Fajar Pradana; Widhy Hayuhardhika Nugraha Putra (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
Competition is an event that is made to be able to facilitate a person or group in improving the quality of their interests and talents. Competition can be divided into three stages as a whole, namely the stage of administrative registration, administrative selection, and the event itself. In general, the developed system has four important processes as solutions to existing problems. The important process includes making a competition conducted by the organizer, registration of the competition for participants who wish to take part in the competition, management of the competition who can determine the competition mechanism following the rules of the organizer organizing the competition. The model used in system development is using SDLC waterfall. The developed system consists of 32 functional requirements that are divided into three different actors. In developing the thesis system, several supporting technologies are used to make it easier to work on the system. Supporting technologies used include the PHP Programming Language, MySQL Database Management System, and the PHP Laravel Framework. The process of developing the system is divided into several structural phases which form the basis of this thesis research method. These phases consist of requirements analysis, system design and implementation, to testing. The testing method used in this research is to use the white box testing method at the unit testing and integration stage, and the black box testing is used in the validation testing stage. The system testing carried out has overall valid results on the test cases that have been made. The test case created is based on the previous stage, namely the needs analysis and system design.